PENERAPANCOGNITIVE LOADTHEORYDALAMSISTEMPEMBELAJARAN - Suhaeniah; Subaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article discusses the application of Cognitive Load Theory (CLT) in thecontext of learning systems aimed at improving the effectiveness of studentlearning processes. Introduced by John Sweller in the late 1980s, the theoryexplains that each individual has a limited capacity to process information.Therefore, it is crucial to manage cognitive load to enable students to learnoptimally. CLT identifies three types of cognitive load: intrinsic load, which isrelated to the complexity of the material; extraneous load, which arises from themethod of presenting information; and germane load, which is related to themental effort that supports the learning process. The application of this theory ineducational practice involves designing instructional materials and learningstrategies that consider students' mental capacities. By avoiding excessiveinformation delivery, using visual aids that support understanding, and organizinginformation effectively, students can focus more on processing relevantinformation. This study employs a literature review method to gather informationfrom various sources related to the implementation of CLT in education. Theresearch concludes that the application of CLT can enhance students'understanding and retention of information. However, challenges in itsimplementation include the need to adjust the material according to students'readiness levels and educators' deep understanding of effective instructionaldesign. In conclusion, the application of CLT is critical for creating a more efficientand effective learning experience.